Glial heterotopia in head and neck, single center experience of 5 cases - Arikeri, Ramyapriyadarshini; Pindicura, Kumudachalam; Namala, Vivekanand; Penta, Ravikumar; Suggula, Ramakrishna; Dandala, Sreedhar Reddy; Tati, Shankar (International Journal of Research in Medical Sciences, 2017)
Background: Heterotopic neuroglial tissue is defined as a mass composed of mature brain tissue isolated from the cranial cavity or spinal canal. The nose and the naso-pharynx are the most common sites of location. Heterotopic masses of neuroglial tissue involving non-midline structures, specifically the middle ear region, are exceptional. In this study, we present four cases of Nasal Glial Heterotopia and a single case of glial heterotopia of the middle ear from the institute. Aim and objective of the study was to study clinicopathological aspects of four cases of nasal glial heterotopia and a rare case of glial heterotopia involving the middle ear. Methods: Neuroglial heterotopias in the head and neck region between 2008 and 2016 were evaluated. Clinical and radiological findings of these cases were analysed. Histopathological examination was the mainstay of diagnosis and Immuno-expression of glial fibrillary acid protein was done for confirmation in few cases. Results: Five cases of glial heterotopias of head and neck were diagnosed during the study period. 4 cases of glial heterotopia of the nasal cavity and one case of glial heterotopia involving the right middle ear, was present in this study. Conclusions: Glial Heterotopias of head and neck are more common in the nasal cavity. Middle ear Glial heterotopias are very rare. Clinical and radiological findings along with histopathology and immuno-histochemistry are essential in diagnosing these lesions.